A Cross-Sectional Study on Nurse-Parent Partnership in the Pediatric Intensive Care Units - Premalatha Paulsamy; Shadia Hamoud Alshahrani; Krishnaraju Venkatesan; Kousalya Prabahar; Manjula Gopinathan Bhagavathy; Mathar Mohideen Nagoor Thangam; Vinoth Prabhu Veeramani; Samya Mohamed Hegazy; Rehab Ahmed; Vigneshwaran Easwaran; Haseena T. A.; Hala A. A.; et al. (International Journal of Clinical Practice)
Aims and Objectives. Admission in the intensive care unit is highly stressful, for both the child and family. This study aimed to identify the factors influencing the nurse-parent partnership in the pediatric intensive care units. Methods. The data were collected from 71 ICU nurses through a web-based survey by the Pediatric Nurse-Parent Partnership (NPP) Scale, Wong and Law Emotional Intelligence (EI) Scale, and patient-centered communication (PCC) proficiency by Park and Oh’s. Descriptive and inferential statistics were used to analyze the data. Results. The mean scores for NPP, EI, and PCC skills were 67.91 ± 9.62, 55.16 ± 5.77, and 33.38 ± 4.81, respectively. There was a positive correlation between NPP, EI (r = 0.71, p<0.001), and PCC skills (r = 0.59, p<0.001). In hierarchical multiple regression analysis, EI (p<0.01) and PCC skills (p=0.05) were the two stronger primary variables influencing NPP than the general variables such as gender, children, and an additional qualification in pediatric nursing with higher variance (59% vs 14%). Conclusion. The findings of the study supported that nurses’ EI and PCC skills as well as additional qualification or training in pediatric nursing were the primary factors influencing nurse-parent partnership in intensive care settings. Thus, effective intervention programs focusing on these factors should be initiated to strengthen NPP.